The firebird - Mackinnon, Mairi; Ugolotti, Sara (Usborne Publishing Ltd. London, 2021)
"One of the most popular Russian folktales, retold for young readers. Who is stealing golden apples from the King's magical orchard? Prince Ivan sets out to find the thief; a journey on which he's helped by Silver Wolf to trace first the Firebird, then the winged Horse of Power, then the princess Marya, held captive by the wicked sorcerer Kaschey. With fun activities after the story, and online audio in both British English and American English. CEFR level: A2. 800 headwords, 2405 words."--Publisher's description